KEBIJAKAN PEMIDANAAN KORPORASI DALAM RUU KUHP: ANALISIS NORMATIF DAN KESIAPAN PRAKTIS APARAT PENEGAK HUKUM - Bulan, Dewi Nawang; Sambas, Nandang (LPPM STIH Awang Long, 2025)
This article analyzes corporate criminal liability policy as stipulated in the Draft of the Indonesian Criminal Code (RUU KUHP). The study focuses on two essential dimensions: the normative construction of corporate criminal responsibility and the practical readiness of law enforcement agencies to implement this policy. Employing a normative legal method with conceptual and comparative approaches, this research finds that despite the progressive legal framework in the RUU KUHP, the institutional and technical readiness of legal practitioners remains limited. Strengthening institutional capacity and drafting comprehensive technical guidelines are crucial to ensure the effective enforcement of corporate criminal liability in Indonesia.